De novo Transcriptome Assembly and Comparison of C3, C3-C4, and C4 Species of Tribe Salsoleae (Chenopodiaceae) - Lauterbach, Maximilian; Schmidt, Hanno; Billakurthi, Kumari; Hankeln, Thomas; Westhoff, Peter; Gowik, Udo; Kadereit, Gudrun (Frontiers in Plant Science, 2017)
C4 photosynthesis is a carbon-concentrating mechanism that evolved independently more than 60 times in a wide range of angiosperm lineages. Among other alterations, the evolution of C4 from ancestral C3 photosynthesis requires changes in the expression of a vast number of genes. Differential gene expression analyses between closely related C3 and C4 species have significantly increased our understanding of C4 functioning and evolution. In Chenopodiaceae, a family that is rich in C4 origins and photosynthetic types, the anatomy, physiology and phylogeny of C4, C2 and C3 species of Salsoleae has been studied in great detail, which facilitated the choice of six samples of five representative species with different photosynthetic types for transcriptome comparisons. mRNA from assimilating organs of each species was sequenced in triplicates, and sequence reads were de novo assembled. These novel genetic resources were then analyzed to provide a better understanding of differential gene expression between C3, C2 and C4 species. All three analyzed C4 species belong to the NADP-ME type as most genes encoding core enzymes of this C4 cycle are highly expressed. The abundance of photorespiratory transcripts is decreased compared to the C3 and C2 species. Like in other C4 lineages of Caryophyllales, our results suggest that PEPC1 is the C4-specific isoform in Salsoleae. Two recently identified transporters from the PHT4 protein family may not only be related to the C4 syndrome, but also active in C2 photosynthesis in Salsoleae. In the two populations of the C2 species S. divaricata transcript abundance of several C4 genes are slightly increased, however a C4 cycle is not detectable in the carbon isotope values. Most of the core enzymes of photorespiration are highly increased in the C2 species compared to both C3 and C4 species, confirming a successful establishment of the C2 photosynthetic pathway. Furthermore, a function of PEP-CK in C2 photosynthesis appears likely, since PEP-CK gene expression is not only increased in S. divaricata but also in C2 species of other groups.